Dilema Perkawinan Adat Sumbawa di Masa Pandemi Covid-19 - Azzulfa, Fatihatul Anhar (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2020)
The procession of traditional marriage is a custom in the community that contains all rituals and require the implementation that must done by many people. The dilemma that occurs in the people of Sumbawa is a problem that must be faced together between the community and the government. This paper tries to explore and examine how the practice of traditional Sumbawa marriage when the Covid-19 pandemic took place in Brang Biji Village, Sumbawa District, Sumbawa Besar Regency. This research is a field research using descriptive analytical method. In this case, the local government has issued a policy during a pandemic Covid-19 to any person who performs his business to always implement health protocols. Meanwhile, the community understands that the traditional marriage procession must always be carried out and the pandemic is not a barrier. The obligation to carry out a traditional marriage procession is not regulated in terms of harmony or marriage conditions, but this customary procession does not contradict Islamic law. Marriage will remain valid if it is carried out in harmony and legal conditions of marriage according to Islamic law without carrying out the traditional procession in marriage. The government should provide an understanding to the community that during the Covid-19 pandemic, traditional marriage processions brought more mafsadah than benefits. Traditional procession becomes less meaningful if it ultimately brings bad consequences to himself or others. [Prosesi perkawinan adat merupakan suatu kebiasaan dalam masyarakat yang berisi segala ritual dan mengharuskan pelaksanaannya dilakukan oleh banyak orang. Dilema yang terjadi di masyarakat Sumbawa menjadi sebuah masalah yang harus dihadapi bersama-sama antara masyarakat dan pemerintah. Tulisan ini mencoba mengeksplorasi serta menelaah bagaimana praktik perkawinan adat Sumbawa saat pandemi Covid-19 berlangsung di Kelurahan Brang Biji Kecamatan Sumbawa Kabupaten Sumbawa Besar. Penelitian ini merupakan penelitian lapangan (field research) yang menggunakan metode deskriptif analitis. Dalam hal ini, pemerintah daerah telah mengeluarkan kebijakan selama pandemi Covid19 bagi setiap orang yang melaksanakan urusannya untuk selalu menerapkan protokol kesehatan. Sementara itu, masyarakat memahami bahwa prosesi perkawinan adat harus selalu dilaksanakan dan pandemi tidak menjadi penghalang. Kewajiban dalam melaksanakan prosesi adat perkawinan tidak diatur dalam rukun maupun syarat nikah, namun prosesi adat ini pun tidak bertentangan dengan Hukum Islam. Perkawinan akan tetap sah jika dilaksanakan dengan rukun dan syarat sah nikah sesuai Hukum Islam tanpa melaksanakan prosesi adat dalam perkawinan. Pemerintah seharusnya memberikan pemahaman pada masyarakat bahwa selama pandemi Covid-19 prosesi perkawinan adat lebih banyak mendatangkan mafsadah daripada kemanfaatan. Prosesi adat pun menjadi kurang bermakna jika pada akhirnya mendatangkan akibat buruk pada diri sendiri atau orang lain.]